Application of functional tests in the evaluation of post-ACL injury performance in athletes: Experience report (Research, Society and Development, 2026)
Anterior Cruciate Ligament (ACL) injury is one of the most frequent injuries in sports, potentially compromising functional performance and increasing the risk of new injuries. In this scenario, assessment through functional tests becomes essential in the return-to-sport process. This study aims to report the experience of applying functional tests to athletes with a history of ACL injury. This is a descriptive experience report, based on the application of the Single Leg Hop Test and Triple Hop Test during sports activities. The experience made it possible to identify asymmetries between lower limbs, highlighting functional deficits in a large part of those evaluated. It is concluded that functional tests are important tools in professional practice, contributing to decision-making for a safe return to sport.